Frontispiece: Phosphorus‐Doped Graphene Oxide Layer as a Highly Efficient Flame Retardant. Issue 44 (23rd October 2015) - Some, Surajit; Shackery, Iman; Kim, Sun Jun; Jun, Seong Chan
<x xml:space="preserve">Abstract</x> Flame Retardant Materials A simple and easy process developed to efficiently dope phosphorus into a graphene oxide surface is reported by S. Some, S. C. Jun et al. in their Communication on page 15480 ff. Phosphorus‐doped graphene oxide (PGO) is prepared by the treatment of polyphosphoric acid with phosphoric acid followed by addition of a graphene oxide solution while maintaining a pH of around 5 by addition of NaOH solution. The as‐made PGO solution‐coated cloth exhibits excellent flame‐retardation properties. This simple technique for direct introduction of phosphorus into the graphene oxide surface to produce phosphorus‐doped oxidized carbon nanoplatelets may be a general approach towards the low‐cost mass production of PGO for many practical applications, including flame retardation.